Separate collection of household food waste for anaerobic degradation – Comparison of different techniques from a systems perspective - Bernstad, A.; la Cour Jansen, J. (Waste management (Elmsford), 2012)
► Four modern and innovative systems for household food waste collection are compared. ► Direct emissions and resource use were based on full-scale data. ► Conservation of nutrients/energy content over the system was considered. ► Systems with high energy/nutrient recovery are most environmentally beneficial. Four systems for household food waste collection are compared in relation the environmental impact categories eutrophication potential, acidification potential, global warming potential as well as energy use. Also, a hotspot analysis is performed in order to suggest improvements in each of the compared collection systems. Separate collection of household food waste in paper bags (with and without drying prior to collection) with use of kitchen grinders and with use of vacuum system in kitchen sinks were compared. In all cases, food waste was used for anaerobic digestion with energy and nutrient recovery in all cases. Compared systems all resulted in net avoidance of assessed environmental impact categories; eutrophication potential (−0.1 to −2.4kg NO3-eq/ton food waste), acidification potential (−0.4 to −1.0kg SO2-eq/ton food waste), global warming potential (−790 to −960kg CO2-eq/ton food waste) and primary energy use (−1.7 to −3.6GJ/ton food waste). Collection with vacuum system results in the largest net avoidence of primary energy use, while disposal of food waste in paper bags for decentralized drying before collection result in a larger net avoidence of global warming, eutrophication and acidification. However, both these systems not have been taken into use in large scale systems yet and further investigations are needed in order to confirm the outcomes from the comparison. Ranking of scenarios differ largely if considering only emissions in the foreground system, indicating the importance of taking also downstream emissions into consideration when comparing different collection systems. The hot spot identification shows that losses of organic matter in mechanical pretreatment as well as tank connected food waste disposal systems and energy in drying and vacuum systems reply to the largest impact on the results in each system respectively.